SITE OF ACTION OF GRAYANOTOXINS IN MAD HONEY IN RATS - YEGEN, BERRAK (JOHN WILEY & SONS LTD, 1991)
Grayanotoxins are known to occur in honey produced from the nectar of Rhododendrons of the family Ericaceae. Grayanotoxins extracted from honey sample obtained from a patient who experienced severe bradycardia and hypotension after ingesting two tablespoonfuls corresponded to Rhododendron ponticum tetrades. Anaesthetized albino rats were injected with honey extract intracerebroventricularly or intraperitoneally. The intracerebroventricular dose was equivalent to 50 mg honey and i.p. doses were equivalent to 50 mg, 1 mg kg-1 and 5 g kg-1 honey. Marked bradycardia and respiratory rate depression were observed in rats injected with extract equivalent to 1 and 5 g kg-1 honey i.p. and in rats injected with 50 mg i.c.v., but not in rats given 50 mg i.p. In bilaterally vagotomized animals, grayanotoxin-contaminated honey extract was not bradycardic. These results suggest that the sites of cardiac and respiratory actions are within the central nervous system, and that the bradycardic effect of grayanotoxin is mediated by vagal stimulation at the periphery.
Keywords: GRAYANOTOXIN; MAD HONEY